Interactive Methods as Means of Ensuring Continuous Professional Development - Soloviova, Olga; Trefanenko, Iryna (My University, 2021)
The present paper aims at discussing the role of interactive methods in modern approach towards continuous professional development of medical students. Inner and outer reasons for switching from a traditional model of education to an innovative one caused popularity of blended education among teachers. Pandemic situation as well as change of education focus from simple acquiring knowledge to getting real life and professional competencies prompt teachers to use new approaches to realization of their students’ potential. We consider interactive methods to be the most effective and valuable for the modern specialist education due to their potential in terms of accessibility and engagement. To succeed in achieving aims of modern education teachers should ensure that methods they choose are activity and personality-oriented, systematic and complex, synergetic and competence-oriented. The research highlights merits of interactive approach and suggests possible ways of usage on the example of a topic from the course of Internal Diseases for medical students.
Keywords: blended education; cooperative learning; professional competencies